Competition-level code generation with AlphaCode - Li, Yujia; Choi, David; Chung, Junyoung; Kushman, Nate; Schrittwieser, Julian; Leblond, Rémi; Eccles, Tom; Keeling, James; Gimeno, Felix; Dal Lago, Agustin; Hubert, Thomas; Choy, Peter; et al. (Science (American Association for the Advancement of Science), 2022)
Programming is a powerful and ubiquitous problem-solving tool. Systems that can assist programmers or even generate programs themselves could make programming more productive and accessible. Recent transformer-based neural network models show impressive code generation abilities yet still perform poorly on more complex tasks requiring problem-solving skills, such as competitive programming problems. Here, we introduce AlphaCode, a system for code generation that achieved an average ranking in the top 54.3% in simulated evaluations on recent programming competitions on the Codeforces platform. AlphaCode solves problems by generating millions of diverse programs using specially trained transformer-based networks and then filtering and clustering those programs to a maximum of just 10 submissions. This result marks the first time an artificial intelligence system has performed competitively in programming competitions.